A study on the status of rural distribution system: traditional vs alternative rural distribution model - Rahman, Abuzar Muhammad Ashrafur (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master of Development Studies, 2008.